To Keep this Disease from Killing You: Cultural Competence, Consonance, and Health among HIV‐positive Women in Kenya. (11th December 2017) - Copeland, Toni
Abstract: The HIV/AIDS crisis continues in sub‐Saharan Africa, where nearly 70% of infections are found. Despite recent efforts to supply antiretroviral therapy to those infected, most are not receiving medication and are forced to rely on self‐management to remain healthy. In Kenya, many of those infected are women living in extreme poverty. This article presents the findings of research among poor women in Nairobi that examined the relationship between knowledge of a cultural model of self‐managing HIV/AIDS, cultural consonance, and health. This biocultural study expands on earlier findings showing that knowledge of the model (competence) is a significant predictor of health by examining here how behavior consistent with that knowledge (consonance) affects health outcomes, as measured by CD4 counts, perceived stress, depressive symptoms, and recent illnesses.